2023
DOI: 10.3390/nu15163507
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Glycemic Index in Children with Type 1 Diabetes

Abstract: In children with type 1 diabetes, a healthy lifestyle is important to control postprandial glycemia and to avoid hyperglycemic peaks that worsen the inflammatory state of vessels and tissues. Glycemic index and glycemic load are two important indexes which assess the quality and quantity of foods consumed during meals. The main macronutrients of the diet have a different effect on postprandial blood glucose levels, so it is important that diabetic children consume foods which determine a slower and steadier gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Postprandial hyperglycemia (PPH) is highly prevalent among people with type 1 diabetes (T1D). High glycemic index (h-GI) meals are mainly responsible for PPH; thus, many clinical practice guidelines recommend a low glycemic index (l-GI) diet for people with T1D [ 1 , 2 , 3 ]. L-GI patterns are associated with improved glycemic control as well as reduced cardiometabolic risk [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postprandial hyperglycemia (PPH) is highly prevalent among people with type 1 diabetes (T1D). High glycemic index (h-GI) meals are mainly responsible for PPH; thus, many clinical practice guidelines recommend a low glycemic index (l-GI) diet for people with T1D [ 1 , 2 , 3 ]. L-GI patterns are associated with improved glycemic control as well as reduced cardiometabolic risk [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A poor adherence to a healthy diet is an everyday struggle and a difficult part of diabetes management among children [ 3 ]. Low-carbohydrate or ketogenic diets have recently become very popular because they ease the glycemic spikes, and provide greater glycemic stability and lower HbA1c values [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adults with T1DM, low-CHO diets reduced postprandial hyperglycemia, improved glycated hemoglobin (HbA1c), increased the time in interval, and reduced the risk of hypoglycemia due to reduced insulin requirements [4]. Studies wherein meal skipping was avoided and a balanced macronutrient intake was realized reported that better metabolic control was achieved and glycemic control was improved [5,6]; therefore, individuals with diabetes should consume foods that set a slower and more stable glycemic peak [7]. Moreover, the recommendation for individuals using continuous glucose monitoring is to spend >70% of the time with sensor glucose values in the range (TIR) (3.9-10.0 mmol/L), <25% of the time above the range (TAR) (>10.0 mmol/L), and <4% of the time below the range (TBR) (<3.9 mmol/L) [8].…”
Section: Introductionmentioning
confidence: 99%